Recent developments in metal/metalloid nanomaterials for battery applications; a comparative review. (15th May 2023) - Ahmad, Awais; Shaheen, Shumila; Majeed, Saadat; Pervaiz, Muhammad; Saeed, Zohaib; Younas, Umer; Javed, Muhammad Sufyan; Luque, Rafael; Gnanasekaran, Lalitha
Highlights: Prospective of nanotechnology in batteries. Recent futuristic in metal/metalloid-based materials synthesis. Metal/metalloid nanomaterials are preferred over the conventional graphitic anode. Future challenges for the development of potential batteries with metal/metalloid-based nanoparticles. Abstract: The global energy demand and consumption have upgraded greatly due to constant population and economic growth. The reinforced investment into solar energy, bioenergy, many other possible fuel technologies, and cost-effective energy storage devices have gained more attention to overcome energy crises. The concept of addressing such a principal challenge latest energy storage devices seems impracticable. To modify and store discontinuous electric output, rechargeable batteries have prompted intensive consideration as stable electrochemical energy storage implements. This review focuses on the prospective of nanotechnology in batteries, particularly with a study of metal/metalloid-based nanoparticles due to their superb physical and chemical properties. In this review, we present a survey of the recent futuristic in metal/metalloid-based materials synthesis, with recent and past advancements in the field. The socioeconomic and scientific benefits are also highlighted. It will explore the comprehensive reason why metal/metalloid nanomaterials are preferred over the conventional graphitic anode due to superb columbic efficacy, long-term stability, and safety. This review article sheds light on the comparison of metal/metalloid nanoparticles including metal–organic framework (MOF), metal alloy, metal oxide, and graphene/metal nanomaterials for electrochemical applications. This review describes the recent research progress during the duration of 2015–2021 in metal/metalloid nanomaterials. The attraction of this review is that it accumulates all the recent data in a single framework which will explore a novel idea for researchers. In concluding the study future challenges for the development of potential batteries with metal/metalloid-based nanoparticles are addressed.